PERDAGANGAN ORGAN TUBUH MANUSIA DALAM PERSPEKTIF HUKUM PIDANA - Muhammad Nur Hamzani (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTACTAs technology develops and advances in time, the world of health is also starting to experience a lot of progress, especially for several diseases that have been found new methods in treatment. For example by discovering new treatment methods by transplanting organs (transplants) for several organs such as kidneys, liver, lungs, and bones. But in practice the method of treatment by transplanting human organs can’t be done easily, bearing in mind that there are still very few organs needed compared to the needs of human organs. Thus causing high prices of a human organ that should not be commercialized, and many people are using this opportunity to meet economic needs by trading human organsThe research method used is normative legal research. Normative legal research is research that studies how the legal norms are. The data collection method uses the library research method. This study uses secondary data obtained from various literature and regulations relating to the problems in this thesis.The results of research or conclusions in this study indicate that the crime of trafficking in human organs has been regulated in several laws but in reality up to now there is only one case of trafficking in human organs that can be disclosed by the authorities. This is because there is still a lack of supervision by the government and the existing legislation still cannot reach the cause of the organ trade itself, so it is necessary to have laws and regulations specifically regulating organ trafficking and transplantation. Keywords: Crime, Human Trafficking, Organs